Amyloid-Beta Interaction with Mitochondria. (30th December 2010) - Pagani, Lucia; Eckert, Anne
Abstract : Mitochondrial dysfunction is a hallmark of amyloid-beta(A β )-induced neuronal toxicity in Alzheimer's disease (AD). The recent emphasis on the intracellular biology of A β and its precursor protein (A β PP) has led researchers to consider the possibility that mitochondria-associated and/or intramitochondrial A β may directly cause neurotoxicity. In this paper, we will outline current knowledge of the intracellular localization of both A β and A β PP addressing the question of how A β can access mitochondria. Moreover, we summarize evidence from AD postmortem brain as well as cellular and animal AD models showing that A β triggers mitochondrial dysfunction through a number of pathways such as impairment of oxidative phosphorylation, elevation of reactive oxygen species (ROS) production, alteration of mitochondrial dynamics, and interaction with mitochondrial proteins. In particular, we focus on A β interaction with different mitochondrial targets including the outer mitochondrial membrane, intermembrane space, inner mitochondrial membrane, and the matrix. Thus, this paper establishes a modified model of the Alzheimer cascade mitochondrial hypothesis.